A Brief Look at the History and Future of the School of Mathematics, Physics and Technology - Curling, Llewelyn R. V.; Oriakhi, Maria; Kemp, Greta (International Journal of Bahamian Studies, 2015)
This paper provides a brief history and overview of the development of the School of Mathematics, Physics and Technology at the College of The Bahamas from the College’s inception in 1974 to 2014. It charts the evolution of the School out of two major departments within the College, highlighting the development of the School’s academic courses, programs and research facilities, in the context of the College’s overall strategic plan toward attaining university status. The paper also chronicles the present and past chairpersons and discusses briefly the significance of Mathematics, Physics and Technology in the context of Science, Technology, Engineering and Mathematics education within the grander framework of the role of COB in providing widespread tertiary education in The Bahamas. The paper celebrates and analyzes the progress of the School in its various earlier incarnations, and its programs over the past 40 years, and provides some thoughts about the directions in which it should go in helping to fulfill the College’s mandate to transition to a university in 2015.